PENINGKATAN KETERAMPILAN MENULIS PERSONAL LETTER MELALUI MODEL PROBLEM BASED LEARNING PADA SISWA KELAS XI SMKS PRIMA WISATA JAKARTA - Haryani, Heni (CV Sintesia, 2024)
This study aims to determine the increase in student learning outcomes with the application of the model Problem Based Learning (PBL). The teacher said that the purpose, main points of learning, carry out group discussions, exercises, give the motivation to learn and a conclusion on the matter of Personal Letter of students of class XI SMK Prima Wisata Jakarta. This research is a classroom action research held in 2 cycles. Each cycle is carried out 2 times the meeting began with the stages of action planning, implementation of action model Problem Based Learning (PBL), and reflection. Method of data collection is done by observation/observation. Data analysis was performed by the comparison between the results of the test in cycle 1 and cycle 2 with the techniques of descriptive. the meaning of the data obtained in this study serve as is then in the descriptive analysis to get an overview of the facts and describe in accordance with the phenomenon. While to measure the learning achievement of students using the system average grade in the results of the evaluation of each cycle. The results showed that the learning outcomes of students of class XI SMK Prima Wisata Jakarta has increased. Cycle I and II (90.26%). The results in cycle II showed that the learning of writing a personal letter by using the model of Problem Based Learning (PBL) on students of class XI SMK Prima Wisata Jakarta goes well and reach the target of mastery in the study of action of this class.